(untitled) (Research, Society and Development, 2020)
In the process of business world growth balanced by the development of technology which is also increasingly rapid. Evidence in the field can be seen on the online trading site. The point is that in buying and selling online there is a process which then arises an agreement that is poured online or electronically. This electronic agreement if analyzed in the world of Notaries and the National Law domain indirectly also influences. The validity of the agreement is still questionable, because none of them are clearly stated in the provisions of the law. In the national law based on the law governing the deed itself, namely the Law of Notary Position and the Civil Code, the application of these provisions will not yet be clearly regulated in both laws. The principle of confidentiality that must be upheld in Article 16 of the LawJN must still be carried out even in making electronic deeds. This study uses a normative juridical method, which describes, explains and at the same time explains the notary liability in upholding the principle of confidentiality in the making of an electronic notary deed. Be an authentic deed or not. Notary liability does not uphold the principle of confidentiality according to Article 16 of the UUJN, the notary must be responsible for all the contents of the deed